RANCANG BANGUN APLIKASI PENJADWALAN HOME SERVICE INDORENT MENGGUNAKAN ALGORITMA FIRST COME FIRST SERVED BERBASIS ANDORID - Prasetiya, Agung (Jurnal Transformatika, 2021)
Android smartphone is one of the items that really help humans in living life today.A person gets information through an internet connection using an Android smartphone whenever and wherever he is. Home Services is a vehicle repair service on site. Thus, customers still get service without leaving activity. The Home Service System is still manual so that it gives customers the opportunity to find out about ordering and scheduling vehicle services. Therefore, the researchers tried to build an Android-based Home Service application using the First Come First Served algorithm to facilitate scheduling. Analytical methods conducted by researchers by collecting data through Literature Studies and Interviews. Thus, resulting in an easier, practical, simple, and efficient Home Services application where customers can schedule vehicle services via an Android Smartphone.
Keywords: Home Service; First Come First Served; Android; Java